Platelet-to-lymphocyte ratio in early onset neonatal - Johnny Lambert Rompis; Rocky Wilar; Gregory Joey; Raynald Octavianus Takumansang; Hesti Lestari (Indonesian Pediatric Society, 2023)
Objectives Neonatal sepsis is a major contributor to morbidity and mortality worldwide. Although blood culture is the gold standard of sepsis diagnosis, it often lacks sensitivity and diagnostic speed. Platelet-to-lymphocyte ratio (PLR) is a widely available, effective, simple, and affordable marker that can predict early onset neonatal sepsis (EONS). Objective To assess the correlation between PLR and EONS as well as the diagnostic value of PLR for predicting EONS. Methods This study included all inpatient neonates with suspected early-onset neonatal sepsis at Dr. R. D. Kandou Hospital, Manado, North Sulawesi, Indonesia. Neonates were categorized into sepsis (confirmed by positive blood culture results) and non-sepsis (negative blood culture results) groups. Bivariate analysis, including the chi-square test for categorical data and independent t-test for numerical data, was performed to identify any significant associations between the platelet-to-lymphocyte ratio (PLR) and EONS. The sensitivity, specificity, and area under the receiver operating characteristic (ROC) curve were calculated to determine the optimal PLR cut-off point to predict EONS. Results In this study, we investigated the relationship between PLR and early-onset neonatal sepsis (EONS) in 176 neonates with suspected EONS. Blood cultures confirmed sepsis in 84 neonates (47.7%), with Klebsiella pneumoniae being the most common causative organism. We found a significant positive correlation between PLR and EONS (p<0.001), and a PLR cut-off point of 61.806 was identified to predict EONS with high sensitivity (90.2%) and specificity (85.7%) Conclusion Our study demonstrates a strong positive correlation between PLR and EONS, and a PLR cut-off point of 61.806 can be used as a valuable marker for predicting EONS in neonates with suspected sepsis. These findings could aid in the early identification and treatment of neonates with sepsis, ultimately improving patient outcomes.